Penetrasi Budaya Korea Selatan terhadap Nilai-Nilai Pancasila: Analisis dari Perspektif Media Sosial di Indonesia - Geprita Gulo; Anisa Asari Dewi; Elvi Maulida Harahap; Fina Febrian; Nurfadhilah Pasaribu; Wildani Putri Sagala; Winda Afdila Sari; Zahwa Maulidina Assyifa; Fazli Rachman (Lembaga Pengembangan Kinerja Dosen, 2024)
Korean culture, especially South Korea, is currently developing very rapidly and widely, resulting in a new phenomenon among teenagers. The much-loved culture is K-Pop, Korean drama(drakor), music, food, and lifestyle. South Korean culture is feared to be the cause of the fading spirit of nationalism among teenagers. The fading of nationalism is a deviation from the values of Pancasila in the third principle which reads